The Influence of Job Stress, Organizational Commitment and Compensation on Nurse Retention in General Hospital Sinar Husni Medan - Pohan, Yuli Arnida; Brina, Melda; Siahaan, Maya; Chandra, Kuandi; Sanjaya, Mega; Tanady, Darwan (PT FORMOSA CENDEKIA GLOBAL, 2025)
Nurse Retention is the company's ability to retain employees who have the potential to remain loyal to the company for a longer period of time. This study aims to determine the effect, work stress, organizational commitment compensation on nurse retention in hospitals. This research is a quantitative study with an associative approach. The population of this study amounted to 80 nurses. In this study, the sample taken was all nurses who were the target of the study, totaling 80 nurses. This study uses multiple linear regression analysis tools equipped with classical assumption tests. Partial analysis results show that job stress, compensation and organizational commitment have a significant effect on nurse retention.